2002
DOI: 10.1002/mds.10123
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of acute levodopa challenge for clinical prediction of sustained long‐term levodopa response as a major criterion for idiopathic Parkinson's disease diagnosis

Abstract: Clinical idiopathic Parkinson's disease (PD) diagnosis requires following strict clinical criteria. Final definitive diagnosis can only be made after pathological confirmation and, despite following clinical criteria, several cases are misdiagnosed. We assessed sensitivity and specificity of acute challenge with levodopa (L-dopa) to predict sustained long-term L-dopa responsiveness as a major criterion for clinical diagnosis of PD. A consecutive series of 82 patients first seen at a movement disorders clinic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 19 publications
5
58
1
2
Order By: Relevance
“…1 In the early stages of the disease, responses to an acute LD challenge reflect chronic LD responsiveness. Moreover, serial LD challenges performed at different stages of disease have helped clarify how the pharmacologic response to LD evolves over the time.…”
mentioning
confidence: 99%
“…1 In the early stages of the disease, responses to an acute LD challenge reflect chronic LD responsiveness. Moreover, serial LD challenges performed at different stages of disease have helped clarify how the pharmacologic response to LD evolves over the time.…”
mentioning
confidence: 99%
“…24 Furthermore, a study of 82 patients, in which the examiner conducting the levodopa chal lenge was blind to the original diagnosis, revealed that the levodopa challenge test had 70.9% sensitivity and 81.4% specificity for predicting a clinical diagnosis of PD. 25 The same study also showed that the specificity of the levodopa test for predicting a clinical diagnosis of PD at early stages of the disease was 100%. 25 The levodopa challenge test is non invasive, costeffective, and easy to administer; tablets of carbidopa-levodopa are taken orally and motor symptoms are scored using the Unified Parkinson's Disease Rating Scale (UPDRS).…”
Section: Box 3 | Casementioning
confidence: 87%
“…25 The same study also showed that the specificity of the levodopa test for predicting a clinical diagnosis of PD at early stages of the disease was 100%. 25 The levodopa challenge test is non invasive, costeffective, and easy to administer; tablets of carbidopa-levodopa are taken orally and motor symptoms are scored using the Unified Parkinson's Disease Rating Scale (UPDRS). These scores are compared with UPDRS scores obtained before levodopa treatmentpractitioners typically expect a 30% improve ment in PD motor sy mptoms.…”
Section: Box 3 | Casementioning
confidence: 87%
See 1 more Smart Citation
“…Paraclinical tests like drug response testing and neurophysiological examinations are routinely employed, but are of limited sensitivity and specificity [3]. Single photon emission tomography and positron emission tomography visualize deficits in central neurotransmission pathways, but lack sufficient specificity and sensitivity to differentiate between PD and AP [4].…”
Section: Introductionmentioning
confidence: 99%